Math, asked by simran29617, 9 months ago

Factorise = 4x² - 2x-2
2​

Answers

Answered by ramandhamija
1

Step-by-step explanation:

4x²-2x-2

by using split middle term

4x²-4x+2x-2

= 4x(x-1)+2(x-1)

(x-1) (4x+2)

so x= 1, -2/4 or -1/2

Answered by omprabhagupta4815
2

Step-by-step explanation:

x2" was replaced by "x^2".

(22x2 - 2x) - 2

4x2 - 2x - 2 = 2 × (2x2 - x - 1)

-2 + 1 = -1

=2x2 - 2x + 1x - 1

=2x × (x-1)

=(2x+1) × (x-1)

Hope this helps you, mark as brainliest :)

Similar questions